Eclogite xenoliths from Orapa: Ocean crust recycling, mantle metasomatism and carbon cycling at the western Zimbabwe craton margin. (15th September 2017) - Aulbach, S.; Jacob, D.E.; Cartigny, P.; Stern, R.A.; Simonetti, S.S.; Wörner, G.; Viljoen, K.S.
Abstract: Major- and trace-element compositions of garnet and clinopyroxene, as well as 87 Sr/ 86 Sr in clinopyroxene and δ 18 O in garnet in eclogite and pyroxenite xenoliths from Orapa, at the western margin of the Zimbabwe craton (central Botswana), were investigated in order to trace their origin and evolution in the mantle lithosphere. Two groups of eclogites are distinguished with respect to 87 Sr/ 86 Sr: One with moderate ratios (0.7026–0.7046) and another with 87 Sr/ 86 Sr >0.7048 to 0.7091. In the former group, heavy δ 18 O attests to low-temperature alteration on the ocean floor, while 87 Sr/ 86 Sr correlates with indices of low-pressure igneous processes (Eu/Eu ∗, Mg#, Sr/Y). This suggests relatively undisturbed long-term ingrowth of 87 Sr at near-igneous Rb/Sr after metamorphism, despite the exposed craton margin setting. The high- 87 Sr/ 86 Sr group has mainly mantle-like δ 18 O and is suggested to have interacted with a small-volume melt derived from an aged phlogopite-rich metasome. The overlap of diamondiferous and graphite-bearing eclogites and pyroxenites over a pressure interval of ∼3.2 to 4.9 GPa is interpreted as reflecting a mantle parcel beneath Orapa that has moved out of the diamond stability field, due to a change in geotherm and/or decompression. Diamondiferous eclogites record lower median 87 Sr/ 86 Sr (0.7039) than graphite-bearing samples (0.7064) and carbon-free samples (0.7051), suggesting that interaction with the – possibly oxidising – metasome-derived melt caused carbon removal in some eclogites, while catalysing the conversion of diamond to graphite in others. This highlights the role of small-volume melts in modulating the lithospheric carbon cycle. Compared to diamondiferous eclogites, eclogitic inclusions in diamonds are restricted to high FeO and low SiO2, CaO and Na2 O contents, they record higher equilibrium temperatures and garnets have mostly mantle-like O isotopic composition. We suggest that this signature was imparted by a sublithospheric melt with contributions from a clinopyroxene-rich source, possibly related to the ca. 2.0 Ga Bushveld event.